Template Independent Synthesis of Nucleic Acid Libraries - D. Bhilare, Kiran; Mohan, Utpal; Chand Banerjee, Uttam (Journal of DNA And RNA Research, 2017)
Though, directed evolution/In vitro evolution has greatly enhanced the applicability of natural biomolecules, there is still a big void in synthetic biology, which could be filled only when we are able to make novel/synthetic functional biomolecules. Terminal deoxyribonucleotidyl transferase (TdT) is the only known DNA polymerase, which can add deoxyribonucleotides without the requirement of a DNA template. Here, we are introducing the concept of Template-Independent Synthesis of Nucleic Acids (TISNA), where we have exploited the property of terminal deoxyribonucleotidyl transferase to add deoxyribonucleotides to the 3’ end of an oligonucleotide for the generation of de novo libraries of ssDNA, dsDNA coding sequences and RNA. We are able to generate libraries that have diversity not only in sequence but also in length in a single library itself. The length of double stranded random gene libraries generated using this approach ranges from 200 base pairs to 10 kilobase pairs. The ability to make random nucleic acid libraries from scratch (independent of any template information) in the laboratory could open up new avenues and holds promise for the pharmaceutical and biotechnological sectors.
Keywords: Gene synthesis; nucleic acid libraries; novel sequence; open reading frames; synthetic biology